SLOWLY MODULATED BAROCLINIC WAVES IN A 3-LAYER MODEL - Moroz, I (1981)
A coupled pair of envelope equations is derived which describe the nonlinear evolution of slowly varying wave packets in a three-layer model of baroclinic instability on a beta-plane. The equations are identical in form to those obtained by Pedlosky (1972) to study wave-packet evolution in a two-layer model. They are transformable to the Self-Induced Transparency equations of nonlinear optics for complex wave amplitude, and to the sine- Gordon equation for real wave amplitude. Both are known to possess soliton solutions, with associated highly predictable behaviour. The three-layer model therefore is another example of a mathematical model of baroclinic instability to exhibit soliton behaviour. The significance of such solutions to meteorology and oceanography is discussed. -Author